2016
DOI: 10.1186/s11671-016-1468-8
|View full text |Cite
|
Sign up to set email alerts
|

Human CIK Cells Loaded with Au Nanorods as a Theranostic Platform for Targeted Photoacoustic Imaging and Enhanced Immunotherapy and Photothermal Therapy

Abstract: How to realize targeted photoacoustic imaging, enhanced immunotherapy, and photothermal therapy of gastric cancer has become a great challenge. Herein, we reported for the first time that human cytokine-induced killer cells (CIK) loaded with gold nanorods were used for targeted photoacoustic imaging, enhanced immunotherapy, and photothermal therapy of gastric cancer. Silica-modified gold nanorods were prepared; then incubated with human cytokine-induced killer cells (CIK), resultant human CIK cells loaded with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 46 publications
1
20
0
Order By: Relevance
“…Enhanced targeting of specific MPS subsets by nanomaterials may decrease off-target effects of drug therapy, improve targeted immunotherapy, and offer treatments for inflammation-driven pathologies like cardiovascular disease (CVD). 1013 …”
mentioning
confidence: 99%
“…Enhanced targeting of specific MPS subsets by nanomaterials may decrease off-target effects of drug therapy, improve targeted immunotherapy, and offer treatments for inflammation-driven pathologies like cardiovascular disease (CVD). 1013 …”
mentioning
confidence: 99%
“…Human CIK cells were expanded from peripheral blood collected from the healthy people in our Laboratory [17]- [22]. All individuals provided informed consent for blood donation according to a protocol approved by the internal review board and ethic committee.…”
Section: Preparation and Identification Of Human Cik Cellsmentioning
confidence: 99%
“…Some reports show that human CIK cells can target in vivo tumor tissues [17]- [22]. However, a lot of reports showed that CIK cells kill tumor cells via releasing some special factors [47,48].…”
Section: Cik Cells Labeled With Pegylated Aunprs For Targeted Fluoresmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, human CIK cells labeled with gold nanorods were used for photothermal-immunological combined therapy of in vivo gastric cancer models, and maximal tumor growth inhibition was achieved. The fact highly suggests that available nanotechnology can be used for enhanced immunotherapeutic efficacy [4]. Cancer nanotechnology or cancer nanomedicine has provided a practical solution for overcoming the limitations of traditional immunotherapy.…”
Section: Daxiangmentioning
confidence: 99%